A Takayasu's Arteritis Case with Unilateral Digital Clubbing - Mahmut ÇİVİLİBAL,; Nilgün SELÇUK DURU,; Gafur DOĞDU,; Murat ELEVLİ,; Semih AYTA1, (Archives of Rheumatology, 2011)
Takayasu arteritis is a large vessel vasculitis that usually affects young female patients during the second and third decades of life. Less commonly, it can also be seen childhood. In this article, we describe a case of Takayasu arteritis in a 17 year-old-boy who presented with unilateral digital clubbing. The patient had also a one-month history of muscle weakness and myalgia in the left upper and lower extremity. There was no hypertension or abdominal bruit. Digital subtraction angiography revealed a total occlusion of the left subclavian artery and a severe narrowing of the right renal artery. The association of digital clubbing and Takayasuʼs arteritis is not common. To our knowledge, only two cases have been reported to date.